Mulheres rurais e plantas medicinais: saberes, socialidades e autonomia feminina - Costa, Juliana de Almeida (2019)
This dissertation presents a study on rural women, settled in settlement projects in Rio Grande do Sul’s land reform, linked to the MST, and the relationships established around medicinal plants knowhow. This research has as its goals to understand how rural women build, from popular health knowledge and practices related to medicinal plants, relationships that provide personal autonomy and emancipation and women rights affirmation in the countryside. This research, built with qualitative approach, is structured on a study based on experiences from five women from different parts of the state, chosen for their pessoal and social achievements around the theme. These rural women were interviewed on a semi-structured script. Furthermore, field notes were used to write down thoughts and observations on field experiences. The following text presents three chapters: the first one analyzes the relation between the knowledge appropriated over these women’s lives and the accumulation around this knowledge as peoples’ cultural heritage, pointing to gender questions around the theme, reflecting around the gendered division of work; the second one studies the transformations built by rural women regarding care and its conceptions, which enables the construction of thoughts facing agroecology and nature care, and symbolic relationships that surround these conceptions.The last chapter analyzes the most recent advances achieved related to public policy institutions, the management of the relationship between rural women and the catholic progressivist sectors and the transformations provided in social spaces among the countryside school community. The knowledge and practice on medicinal herbs are understood by these women as a chance to do good and as a heritage that must be passed to new generations. With the knowledge and practices on medicinal herbs, rural women transformed the conception of care, making it wide and linked to all living beings and nature. The relationships these women build with several social agents, linked to distinct institutions, reinforce their personal autonomy and give them the opportunity to fill important social spaces that strengthen the process of social emancipation and women’s rights in the countryside.